Modulation of endothelial responses by the stromal microenvironment: effects on leucocyte recruitment. (25th October 2007) - McGettrick, H.M.; Filer, A.; Rainger, G.E.; Buckley, C.D.; Nash, G.B.
Abstract : Vascular endothelial cells play a pivotal role in regulating leucocyte recruitment during inflammation, and their responses can be modulated by their local environment, including cells of the tissue stroma. We have developed a model system to examine how the communication between endothelial cells and fibroblasts regulates the recruitment of leucocytes and their subsequent subendothelial fate. Here, we describe a novel co-culture filter-based flow assay and highlight the ability of synovial fibroblasts obtained from chronically inflamed tissue to promote leucocyte recruitment to otherwise 'resting' endothelial cells.